FEA-based metal sphere signal map for mass estimation of simulated loose part in reactor coolant system. (July 2018) - Moon, Seong-In; Kang, To; Han, Soon-Woo
Abstract: For safety management of nuclear power plants, accurate impact mass estimation of loose parts is very important. A center frequency method based on Hertz's impact theory, a frequency ratio method, and so forth are studied for mass estimation, but it is known that these approaches can hardly provide accurate information on impact response for identifying the impact source. In this paper, a finite element analysis (FEA) model to simulate the propagation behavior of the bending wave, generated by a metal ball impact, was validated by performing a series of impact tests and the corresponding finite element analyses for a flat plate as well as a curved plate (a half scale model of steam generator vessel). Various impact parameters such as amplitude, center frequency, group velocity and attenuation ratio of bending wave acceleration signal were investigated to verify the usefulness of the FEA model. Also, an FEA-based metal sphere signal map was developed, and then blind tests were performed to verify the map. This study provides an accurate simulation method for predicting the metal impact behavior and for building a metal sphere signal map, which can be used to estimate the mass of loose-parts on site in nuclear power plants.